Gallegos, gombadres e negócios: os imigrantes libaneses na Praça Mercantil da cidade de Fortaleza-CE (1890 – 1930) - Franklin, Ruben Maciel (2011)
This research intend to analyze the constitution of sociability networks between Lebanese immigrants in the Fortaleza, state of Ceará in Brazil, in the last years of the nineteenth century and beginning of the twentieth, when the growth of the commerce was opening a lot of possibilities for investments and a lot of traders were interesting in important sectors, for example: dresses, shoes and others jewel accessories. So, favorable contexts for the immigrants sell merchandises and get their own stores. The notion of migration networks helps us to study the associative binds where the Lebanese dislocated through of contacts sustained between patricians. In this way, the peddler was the principal activity of these fellows, when some of them enriched and helped fellow countryman/woman recently arrived. This movement was still linked the motivations about the choices of the Lebanese for the urban occupations and for the kind of professional specialization: cloths and sundries. Afterward, I also looked for to create some questions about social organization these immigrants in the commerce and how they negotiated their positions inside local hierarchy.